Problems of a code of conduct - Karl Wolfgang Menck (Intereconomics, 1975)
UNCTAD's Main Committee for Technology is to meet in November 1975 to discuss once again the subject of a Code of Conduct to be observed in transferring technical knowledge. What chances are there for such a Code to be adopted?
Keywords: 330; Technology Transfer